An Industrial systems design study on SCT Furnishing Corporation - Jiao, Felise Isabel; Tan, Bernice Pearl; Velasquez, Gabriel; Yap, Lisa Angela (College of Engineering, 2005)
SCT Furnishing Corporation is a medium-sized manufacturer and exporter of wood furniture for commercial establishments. It was established in 1977 and currently caters to the Japanese and Dutch Markets. SCT also caters to the local market by maintaining two showrooms located t MC Home Depot at Ortigas and at The Fort. The total system approach was used to conduct this Industrial Systems Design Study on SCT Furnishing Corporation. After documenting the company's mission, vision, and current strategies, its external environment was assessed using industry and competitor analyses, and Porter's Five Forces Model. With knowledge of its external environment, SCT's current business position was then analyzed using SWOT analysis. The results of the SWOT analysis includes the strengths of custom made designs and having a wide range of materials, the opportunities of the Philippine and European market, the weaknesses of its limited production capability, and its low prioritization for human resource management, and the threats of lean seasons and the log ban. From these, a gap analysis was conducted to reveal strategies that would bridge the gap between SCT's current and envisioned states. The gap analysis resulted in the following key strategies that SCT should employ: 1) Strengthen local presence through the showroom-Based on a comparison of different marketing alternatives, it is recommended that SCT join the annual Philippine Furniture Festival and that they engage in aggressive marketing through flyers, brochures, and catalogs. Doing so would increase the showroom's combine revenues by PhP 235,000 per month. 2) Develop better employee packages, incentives, and safety measures to improve employee performance and motivation-A number of easily implemented recommendations were proposed. Among those ranked with higher priority are the use of personal protective equipment such as safety goggles, masks and earplugs, the implementation of performance measurement tools such as performance ratings, project-based bonuses and monthly recognitions, and the introduction of non-cash gain sharing compensation plans and focus group discussions. 3) Standardize capacity determination-A procedure for measuring SCT' capacity and the capacity requirement per project was outlined and illustrated. By using this procedure, SCT will be able to accurately determine its available capacity which will help them in making decisions in accepting and rejecting new projects. Other benefits include improved production schedules and more accurate piece-rate standards. 4) Create disaster-recovery plan for the log ban-In response to the impending log ban issue, a set of possible plans of action and their corresponding payoffs for different possible events concerning the log ban were identified. With the objective of overall company sustainability, the minimax regret criterion for decision analysis showed that engaging in product diversification will be most beneficial for SCT in the long run. Doing so allows SCT to continue its current wood furniture line while being able to enter into the market of furniture made of alternative materials, which based on recent trends, will be very large in the future.